Perlindungan Hukum Hak Merchandising dalam Menunjang Pertumbuhan Industri Kreatif di Indonesia dihubungkan dengan Undang-Undang Nomor 19 Tahun 2002 Tentang Hak Cipta - Muhammad Djumhana (Fakultas Hukum, Universitas Islam Bandung, 2010)
A merchandise is protected by the intellectual property rights regime over creative copy rights, known as merchandising rights. Basically, merchandise product and trade use the main components of an intellectual work in the field of copy rights, trade-mark rights, industrial design rights and other intellectual property rights. Legal protection over merchandising rights in Indonesia is not regulated by the existing laws and regulations relating to intellectual property rights. In this context, Law No. 19 of 2002 on Copy Rights does not specifically regulate the provision of merchandising rights. The absence of such provision and the law enforcement weakness in this area is unexpected condition by industrial-creative business actors. This article will seek to demonstrate gaps in the current legal framework on intellectual property rights providing legal protection over merchandising rights.